Unveiling the potentials and action mechanisms of Citri reticulatae Pericarpium as an anti‐inflammatory food - Yanyi Li; Ying Chen; Yue Zhou; Jiayi He; Qian Zhou; Mingfu Wang (Food Frontiers)
Abstract Modern lifestyle has led human body under a frequent exposure of chronic inflammation. Intriguingly, extensive studies have indicated that Citri reticulatae Pericarpium (CRP), the dried peel of Citrus reticulata Blanco and its cultivated varieties, has immense potential as an anti‐inflammatory food. Therefore, the present review aims to summarize advances in utilizing CRP for the prevention and controlling of inflammation under various pathological conditions. In particular, this review provides a comprehensive overview of the bioactive compounds present in CRP, with a specific focus on polymethoxyflavones and their transformations during aging process. Moreover, the underlying mechanism responsible for the anti‐inflammatory effects primarily involves the inhibition of inflammatory factors through signaling pathways, such as mitogen‐activated protein kinases and nuclear factor‐erythroid 2‐related factor 2–antioxidant pathways. The interaction with gut microbiota also contributes to the anti‐inflammatory potential of CRP. In summary, this review offers valuable insights into the health benefits of CRP and its constituents, laying a solid foundation for the further development of CRP into anti‐inflammatory foods.